Comparison of the Effectiveness of Emotion-Focused Therapy and Cognitive-Behavioral Therapy on Family Functioning and Attitudes Toward Extramarital Relationships in Infertile Marginalized Women in Tehran - Fadaei, Mona; Akbari, Bahman; Moghtader, Leila (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to compare the effectiveness of Emotion-Focused Therapy (EFT) and Cognitive-Behavioral Therapy (CBT) on family functioning and attitudes toward extramarital relationships in infertile marginalized women in Tehran. Methods and Materials: The research method was quasi-experimental with a pretest–posttest design, a two-month follow-up, and a control group. The statistical population included all infertile women who attended the clinic of Dr. Elina Bayramzadeh (gynecologist, obstetrician, and infertility specialist) in the second half of 2024. Out of 120 screened individuals, 45 participants were randomly assigned to three groups (15 in each): two experimental groups (EFT and CBT) and one control group. Research instruments included the Whatley Attitudes Toward Infidelity Scale (2006) and the Family Assessment Device by Epstein et al. (1983). Data were analyzed using mixed-design ANOVA and Bonferroni post hoc tests in SPSS-26. Findings: Findings indicated that both interventions significantly improved family functioning and reduced attitudes favorable to extramarital relationships (p < .05). However, Emotion-Focused Therapy demonstrated greater effectiveness compared to Cognitive-Behavioral Therapy (p < .002). The effect size of EFT for family functioning (η² = .68) and attitudes toward extramarital relationships (η² = .81) was significantly larger than that of CBT. Moreover, the effects of both interventions remained stable at the follow-up stage. Conclusion: It was concluded that both therapeutic approaches are effective; however, Emotion-Focused Therapy holds superiority, particularly in enhancing emotional and relational variables. These findings can inform the design of targeted psychological interventions for infertile marginalized women.